2017
DOI: 10.1016/j.athoracsur.2016.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Upregulation of Cyclooxygenase 2 Contributes to Altered Coronary Reactivity After Cardiac Surgery

Abstract: Background We hypothesized that upregulation of inducible cyclooxygenase 2 (COX-2) contributes to altered coronary arteriolar reactivity early after cardioplegic arrest and cardiopulmonary bypass (CP/CPB) in patients with diabetes mellitus who are undergoing cardiac surgery. Methods The right atrial tissue samples of non-diabetes (ND), controlled diabetes (CDM), and uncontrolled diabetes (UDM) patients undergoing cardiac surgery were harvested before and after CP/CPB. Coronary arterioles (80 to 150 mm) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 27 publications
3
15
0
Order By: Relevance
“…These novel findings suggest that diabetes markedly enhances COX-2 activation in the peripheral microvasculature, indicating that COX-2 may play an important role in the vasodilation pathway involving bradykinin in the peripheral microcirculation early after CPB. Consistent with our previous study in the ischemic heart and coronary microvasculature, 10,11,16 we found upregulation of COX-2 protein expression in the skeletal muscle and peripheral arterioles in the diabetic patients at baseline. In addition to the Western blot experiments, immune-histochemical staining also detected enhanced skeletal muscle and vascular localization of COX-2 in diabetic patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These novel findings suggest that diabetes markedly enhances COX-2 activation in the peripheral microvasculature, indicating that COX-2 may play an important role in the vasodilation pathway involving bradykinin in the peripheral microcirculation early after CPB. Consistent with our previous study in the ischemic heart and coronary microvasculature, 10,11,16 we found upregulation of COX-2 protein expression in the skeletal muscle and peripheral arterioles in the diabetic patients at baseline. In addition to the Western blot experiments, immune-histochemical staining also detected enhanced skeletal muscle and vascular localization of COX-2 in diabetic patients.…”
Section: Discussionsupporting
confidence: 92%
“…16 In the present study, we observed that bradykinin-induced vasodilation of the skeletal muscle arterioles was partially via COX-2 activation in diabetic patients, but not in non-diabetic patients at baseline. Importantly, after CPB, bradykinin-induced relaxation response was inhibited in the presence of the selective COX-2 inhibitor NS398 in both ND, and DM arterioles, whereas this effect was more pronounced in the DM group.…”
Section: Discussionmentioning
confidence: 38%
See 1 more Smart Citation
“…The COX2 and NOS3 gene polymorphisms alter COX2 and NOS3 gene expression, as well as cyclooxygenase and nitric oxide synthesis. Cyclooxygenase and nitric oxide are important mediators of the inflammatory response in diabetes . Low grade inflammation has been shown to play a significant role in the pathogenesis of GDM …”
Section: Discussionmentioning
confidence: 99%
“…Cyclooxygenase and nitric oxide are important mediators of the inflammatory response in diabetes. [23][24][25][26][27] Low grade inflammation has been shown to play a significant role in the pathogenesis of GDM. [3][4][5] Apgar (0-10) 9.9 ± 0.4 9.7 ± 1.0…”
Section: Discussionmentioning
confidence: 99%